Positive Influence of a Probiotic Mixture on the Intestinal Morphology and Microbiota of Farmed Guinea Fowls (Numida meleagris) - Galosi, Livio; Desantis, Salvatore; Roncarati, Alessandra; Robino, Patrizia; Bellato, Alessandro; Nebbia, Patrizia; Ferrocino, Ilario; Santamaria, Nicoletta; Biagini, Lucia; Filoni, Lorenzo; Attili, Anna Rita; Rossi, Giacomo (Frontiers in Veterinary Science, 2021)
To understand the effectiveness of a probiotic mixture on intestinal morphology, mucus layer composition and caecal microbiota diversity, forty10-days old Guinea fowls (Numida meleagris) were assigned to two groups: control group (C), receiving drinking water, and treated group (P), receiving water plus a commercial multi-strains probiotic (Slab51®, 2x1011 UFC/L). Birds were slaughtered after four months and intestines were collected. Samples from duodenum, ileum and caecum were processed for morphological and morphometric studies, and conventional glycohistochemistry. Caecal samples were also used to assess the microbiota by 16S metataxonomic approach. Group P showed significant increase of villus height (p < 0.001 in duodenum and p < 0.05 in ileum and caecum), villus width (p < 0.05 in all investigated tracts), depth of crypts (p < 0.001 in duodenum and caecum; p < 0.05 in ileum), and goblet cells per villus (p < 0.001 in all investigated tracts) as compared with group C. Caecal microbiota of birds varied considerably and comparing the relative abundance of the main Observational Taxonomic Units (OTUs), a positive enrichment of several beneficial taxa like Oscillospira, Eubacterium, Prevotella and members of the Ruminococcaceae was observed. High levels of diversity can improve microbiota stability and resilience facing environmental stresses, enhancing its resistance against invading pathogens. Ruminococcaceae, which represent the most important taxon in both groups, and Prevotella have a key role in the gut physiology due to the production of short-chain fatty acids (SCFAs), that are a vital energy source for enterocytes, improve glucose metabolism and exert an overall anti-inflammatory effect. Probiotic administration enriches presence of Coprococcus, Oscillospira and Eubacterium taxa, that produce butyrate, which exerts a beneficial effect on growth performance, structure of villi and pathogen control and has anti-inflammatory properties too. This study indicates that Slab51® supplementation positively affects the morphology and microbiota diversity of Guinea fowl intestine.